Facilitators Of Internet Promotion (E-Brochure) Adoption By Non-Profit Organisations - Ndubisi, Nelson Oly (Asian Academy of Management (AAM), 2005)
Internet promotion, otherwise e-brochure (EB) or partial e-commerce adoption by nonprofit organisations denotes the use of the Internet to provide business and service related information by academic institutions (as in the present study), non-profit organisations, religious organisations, and government agencies to reduce their expenses or to improve their operations and customer service. A field survey of Malaysian universities was conducted to determine the key factors that facilitate the adoption of non-business EB. Since EB adoption decision is a strategic one, a comprehensive list of potential facilitators for the strategic use of information technology (IT) was derived from extant literature and used in collecting data from 65 schools and centres in five public universities in Kota Kinabalu and Kuala Lumpur, Malaysia. The data were factoranalysed to determine the key underlying dimensions of facilitators. On the basis of the resulting five dimensions namely, relative advantage orientation, network orientation, information efficiency orientation, innovativeness orientation, and competitiveness orientation, regression analysis was done to determine the impact of the five dimensions on non-business EB adoption.